The presidency - Pious, Richard M. 1944- (Ballots and bandwagons, 1991)
Examines how the office and functions of the Chief Executive have evolved over two centuries, focusing on prominent administrations such as those of Washington, Lincoln, FDR, and the modern era of "imperial" and "media" presidencies.